From Historical Materialism to the Philosophy of Praxis: Gramsci and “the New Philosophy” - Grimaldi, Giorgio (International Gramsci Journal, 2024)
Gramsci’s use of the expression – taken from Labriola – «philosophy of praxis» is a terminological shift (from «historical materialism») that implies a complex content that needs to be explored. All the terms (materialism/historicism, philosophy/praxis) need to be developed in their inner correspondences and connections. In particular, the transition from “history” to “philosophy” is particularly relevant: they converge through “praxis”. This paper will focus on the value that the expression “philosophy of praxis” acquires thanks to Gramsci’s reflections. It is an innovative meaning, a turning point that Marxism has produced in the history of thought. But at the same time, the “philosophy of praxis” is the heir of an “operative” thought that has a long background. It thus becomes the critical heir not only of a tradition, but also of some of the most important moments in the history of thought as a whole, orienting it towards an absolute immanence.